Understanding the expansion of Italian metropolitan areas: A study based on entropy measures. (February 2022) - Altieri, Linda; Cocchi, Daniela
This work presents a study on the urban configuration of a number of Italian metropolitan areas and their development over time, with the aim of evaluating the size and shape of urban areas expansion. Raster data are used, produced by the European Environmental Agency within the COoRdination of INformation on the Environment land cover project. The study is based on a version of spatial entropy measures proposed and validated by a recent series of papers, aimed at the evaluation of spatial data heterogeneity; the methods assess the efficiency of the spatial configuration of urban areas. An innovative combination of two entropy measures is the tool for evaluating the urban development in Italy. Results allow both conclusive comments about each metropolitan area and comparisons across areas over space and time.